Literature Circle Strategy for Grade 10 Learners Of Bigaa Integrated National High School - Burgos, Maria Pamela P. (Researchparks Publishing, 2025)
This study confronts the persistent literacy challenges faced by Grade 10 students, demonstrating the potential of literature circles as a dynamic and student-centered instructional approach. Literature circles create a structured yet engaging environment where students collaboratively explore texts, engage in thoughtful discussions, and refine their critical thinking skills. Through these interactions, learners not only enhance their reading comprehension but also develop the confidence to articulate their ideas and engage meaningfully with their peers. To evaluate the impact of this method, a quasi-experimental research design was conducted at Bigaa Integrated National High School. A pretest and posttest were administered to assess students’ literacy skills before and after the implementation of literature circles. The collected data underwent statistical analysis using the mean, independent t-test, and dependent t-test, revealing a significant improvement in students’ literacy performance. These findings underscore the value of literature circles in fostering deeper learning experiences and addressing literacy gaps, reinforcing their potential as an effective educational strategy.